2019
DOI: 10.1177/2381468319892237
|View full text |Cite
|
Sign up to set email alerts
|

How Should the Value Attributes of Novel Antibiotics Be Considered in Reimbursement Decision Making?

Abstract: Antibiotics have revolutionized the treatment of bacterial infections. However, it is widely held that there is underinvestment in antibiotics research and development relative to the socially optimal level for a number of reasons. In this article, we discuss whether existing health technology assessment procedures recognize the full economic and societal value of new antibiotics to patients and society when making reimbursement decisions. We present three recommendations for modelling the unique attributes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…This approach was adopted, for instance, in an economic evaluation of a new antibiotic to treat intensive care unit patients infected with Acinetobacter baumannii ( Rothery et al, 2018 ). In another economic evaluation, transmission and diversity value was incorporated by adding related costs and health outcomes to the numerator and denominator, respectively, of the incremental cost-effectiveness ratio of the antibiotic ( Morton et al, 2019 ).…”
Section: Aggregating Value Elementsmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach was adopted, for instance, in an economic evaluation of a new antibiotic to treat intensive care unit patients infected with Acinetobacter baumannii ( Rothery et al, 2018 ). In another economic evaluation, transmission and diversity value was incorporated by adding related costs and health outcomes to the numerator and denominator, respectively, of the incremental cost-effectiveness ratio of the antibiotic ( Morton et al, 2019 ).…”
Section: Aggregating Value Elementsmentioning
confidence: 99%
“…Furthermore, the experience with antibiotic assessment practices in Europe indicates that the different value elements of antibiotics are not taken into account systematically by reimbursement agencies and, at best, are considered in a qualitative manner. For instance, surveys have shown that the impact on antimicrobial resistance has been mentioned or implied in economic evaluations of individual antibiotics submitted to reimbursement agencies, but this and other values were not incorporated in a structured way in the ultimate decisions ( Charafi and Chen, 2017 ; Morton et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some countries are examining the potential to adjust the prices of new antibiotics to be commensurate with the value not only for the patient but also society. Several different types of indirect societal values have been described and formulas devised, including transmission value (an antibiotic’s ability “to reduce transmission rates in the general population”) and diversity value (an antibiotic’s potential “to curb resistance through a reduction in selection pressure”) [ 19 , 20 ]. Including indirect effects may allow an antibiotic to achieve a higher unit price.…”
Section: Diagnosis-related Groups (Drg) Carve-outmentioning
confidence: 99%